Odpowiedź :
a) [(x^8*y^4)*y^3] / x^7 = x^1 *y^7 = -1 *-3^7
b) [(x^2*y^3)^2 *y^4] / x^7 = [x^4*y^6*y^4]/x^7 =[x^4*y^10]/x^7=
[-2^4*(-1)^10)]/-2^7 = 16/128
b) [(x^2*y^3)^2 *y^4] / x^7 = [x^4*y^6*y^4]/x^7 =[x^4*y^10]/x^7=
[-2^4*(-1)^10)]/-2^7 = 16/128
a)
[(-1)⁴*(-3)²]²*(-3)³ (1*9)²*(-27) 81*(-27) -2187
=__________________=_____________=_________=______=2187
(-1)⁷ (-1) (-1) -1
b)
[(-2)²*(-1)³]²*(-1)⁴ [4*(-1)]²*1
=_________________=______________=-16/128=-1/8
(-2)⁷ -128
[(-1)⁴*(-3)²]²*(-3)³ (1*9)²*(-27) 81*(-27) -2187
=__________________=_____________=_________=______=2187
(-1)⁷ (-1) (-1) -1
b)
[(-2)²*(-1)³]²*(-1)⁴ [4*(-1)]²*1
=_________________=______________=-16/128=-1/8
(-2)⁷ -128